Quantitative analysis of performance on a progressive-ratio schedule: effects of reinforcer type, food deprivation and acute treatment with Δ⁹-tetrahydrocannabinol (THC) - Olarte-Sánchez, Cristian; Valencia-Torres, L.; Cassaday, Helen J.; Bradshaw, Chris; Szabadi, Elemer (Elsevier, 2015)
Rats’ performance on a progressive-ratio schedule maintained by sucrose (0.6 M, 50 μl) and corn oil (100%, 25 μl) reinforcers was assessed using a model derived from Killeen’s (1994) theory of scheduled-controlled behaviour, ‘Mathematical Principles of Reinforcement’. When the rats were maintained at 80% of their free-feeding body weights, the parameter expressing incentive value, a, was greater for the corn oil than for the sucrose reinforcer; the response-time parameter, δ, did not differ between the reinforcer types, but a parameter derived from the linear waiting principle (Tₒ), indicated that the minimum post-reinforcement pause was longer for corn oil than for sucrose. When the rats were maintained under free-feeding conditions, a was reduced, indicating a reduction of incentive value, but δ was unaltered. Under the food-deprived condition, the CB1 cannabinoid receptor agonist Δ⁹-tetrahydrocannabinol (THC: 0.3, 1 and 3 mg kg-1) increased the value of sucrose; none of the other parameters was affected by THC. The results provide new information about the sensitivity of the model’s parameters to deprivation and reinforcer quality, and suggest that THC selectively enhances the incentive value of sucrose.